Conflits Armes Et Representativite Ethnique Au Nord-Kivu En Republique Democratique Du Congo - Bahama, Tabin Lissendja (European Scientific Journal, ESJ, 2017)
The goal pursued in the present reflection is to analyze and explain the relationship of cause and effect between the persistence of armed conflicts and the issue of ethnic representation in political institutions in North-Kivu in Democratic Republic of Congo. Since the 1990s, is observed a systematic use of ethnicity in the calculations of political, economic and social actors active in the province. In addition to the question of nationality of immigrants, access to land and overpopulation, the question of representation of ethnic groups arises with acuity and remains at the center of the attitudes and behaviour of political and security actors on the ground. The elections held in the country in 2006, leading to the no representativeness of the tutsi ethnic group, have reconfigured the dominant positions available since the advent of rebellions in the country. An attempt to maintain or regain their status as, gun violence has been used by stakeholders, leading to the reactivation of the other ethnic dormant for the construction of bands armed self-defence groups. The persistence of the conflict in North Kivu in recent years would be also linked to the violent struggle triggered by members of the tutsi ethnic group in order to ensure their representation in provincial institutions of North Kivu, central Government or even in other strategic positions in the country. This gives political and security logically motivated other ethnic local to replenish the armed groups in order to address the threat of domination that tries to impose the tutsi ethnic group in North-Kivu.